ANALYSIS OF EMPLOYEE RETENTION STRATEGY AT CV. dr. BL SKINCARE IN BEKASI, WEST JAVA - Lutam, Alin Michael; Saerang, David P.E; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract:  Such  as  the  implementation  of  the strategy  at  CV  dr  BL  Skincare  that  is  not  in  accordance  with  existing  work  standards  or  standard  operational procedure  (SOP).  This  research  aims  to  identify  how  the  employee  retention  strategy  at  CV  dr  BL  Skincare Bekasi,  in  West  Java.  Type  of  this  research  approach  is  descriptive  with  qualitative  method  is  applied  in  this research  since  there  will  be  observation  and  in-depth  interview  needed  as  a  tool  to  gather  data  and  analysis.  The sample  used  saturated  sampling   method  and  only  will  be  used  in  a  small  population  such  as  employees  and  dr. Between  Lutam  as  the  owner  at   CV  dr  BL  Skincare,  which  is  there  are  7  informants  in  this  research  in-depth interview.  There  are  five  indicator  will  be  used  in  in-depth  interview  there  are;  Nature  of  Work,  Remuneration, Flexible  Working  Hour,  Team  Relationship,  and  Job  Security.  The  result  employees  at  CV  dr  BL  Skincare  think that  employee  retention  strategy  in  indicator  remuneration  is  important  there  must  be  change.  The  strategy  that being  used  situational  salary  at  least  up  even  if  it  does  not  follow  UMP  Bekasi  West  Java.  From  the  result  the researcher  suggests  are  made  the  employees  are  not  satisfied  with  their  remuneration  provided  by  the  organization.Keywords: human  resources,  employee  retention  strategy